An assessment of economic and environmental impacts of refugees in Nakivale, Uganda - Alex Ronald, Mwangu (Routledge Taylor and Francis group, 2020)
Uganda is one of the leading host countries for refugees in the East and Horn of Africa. Uganda’s location among instable neighbouring countries and its open door policy to refugees has seen a big number of refugees flowing into the country from Southern Sudan, Rwanda, Somalia, Burundi, Eritrea, Kenya, Ethiopia and Democratic Republic of Congo. Some of the refugees are hosted in Nakivale one of the biggest refugee camps in the country located in South Western Uganda. This paper documents the economic and environmental impacts of refugees in Nakivale refugee camp. Data were generated through Focus Group Discussion and interviewing camp leaders, government officials, local leaders, the refugees and community members. This paper contends that the establishment and dense occupancy of Nakivale refugee camp have exerted pressure on the environment as the refugees’ endeavor to revitalize their livelihoods. The increasing numbers of refugees and their active involvement in the production systems has had an impact on the economy. The government should harmonize the interpretation of the 2006 Refugee Act on the right of refugees to employment so that they can increasingly be engaged in production systems, sizes of land allocations should be increased to facilitate expansion in economic activities; and scale up the environment management aspects that has been rolled out in new Uganda Development Response to Displacement Project